Pengaruh Tingkat Pemahaman Terhadap Hasil Belajar Mata Pelajaran Akuntansi Pada Siswa Kelas X Di SMK Negeri 1 Kota Bengkulu - Sazili, Sazili; Selviani, Ayudho; Handayani, Mely (Jurnal Multidisiplin Dehasen (MUDE), 2025)
This study aims to determine whether there is an effect of accounting. This study used quantitative methods. The population in this study were students of Class X accounting expertise program SMK Negeri 1 Kota Bengkulu, with a sample of 41 students determined through Strativied Sampling technique. This data collection technique is done through questionnaires and documentation of final Semester exam scores. The results of the analysis showed that the level of student understanding is in the category of" good "with an average score of 31.07, while learning outcomes are in the category of" good " with an average score of 32.31. However, based on the results of the t-test and F-test, a significance value of 0.196 (> 0.05) was obtained, which means that there is no statistically significant effect. The value of the coefficient of determination (R2) of 0.043 indicates that the level of understanding only explains 4.3% of the variation in learning outcomes, while 95.7% is influenced by other factors outside this study. Thus, although there is a positive relationship, the influence of the level of understanding on learning outcomes is considered weak and insignificant.